T4-Related Bacteriophage LIMEstone Isolates for the Control of Soft Rot on Potato Caused by ‘Dickeya solani’ - Adriaenssens, Evelien M.; Van Vaerenbergh, Johan; Vandenheuvel, Dieter; Dunon, Vincent; Ceyssens, Pieter-Jan; De Proft, Maurice; Kropinski, Andrew M.; Noben, Jean-Paul; Maes, Martine; Lavigne, Rob (PloS one, 2012)
The bacterium 'Dickeya solani', an aggressive biovar 3 variant of Dickeya dianthicola, causes rotting and blackleg in potato. To control this pathogen using bacteriophage therapy, we isolated and characterized two closely related and specific bacteriophages, vB_DsoM_LIMEstone1 and vB_DsoM_LIMEstone2. The LIMEstone phages have a T4-related genome organization and share DNA similarity with Salmonella phage ViI. Microbiological and molecular characterization of the phages deemed them suitable and promising for use in phage therapy. The phages reduced disease incidence and severity on potato tubers in laboratory assays. In addition, in a field trial of potato tubers, when infected with 'Dickeya solani', the experimental phage treatment resulted in a higher yield. These results form the basis for the development of a bacteriophage-based biocontrol of potato plants and tubers as an alternative for the use of antibiotics.